THE SOCIO-ECONOMIC AND POLITICAL FOUNDATIONS OF NIGERIA’S FOREIGN POLICY DURING THE SECOND REPUBLIC: LESSONS AND ALTERNATIVES FOR THE 21ST CENTURY - Adenipekun, Lawrence Olu (Journal of Contemporary International Relations and Diplomacy, 2021)
This study examines the socio-economic and political foundations of Nigeria’s foreign policy during the Second Republic and their lessons in charting a new path in the 21st Century. It explores how neo-colonialism, within the context of an international capitalist economy, intensified class antagonism, socio-economic and political contradictions, which impinged negatively on the foreign policy initiatives and postures of Nigeria between 1979 and 1983. Drawing insights from the Marxist political economy approach, this fresh study departs from the common orientation of economic determinism by focusing on the complex interplay between the political, economic and social subsystems through the historical materialist approach to which little attention has hitherto been paid. The study made use of primary data through the conduct of interviews and also relied on secondary sources. The study found that the distorted and peripheral role of dependent neo-colonial Nigeria in the world capitalist economy, its sole reliance on oil and the neglect of agriculture generated socio-political and economic crises that constrained it from pursuing viable foreign policy goals during the period under study. The paper concluded that the pursuit of bold and impactful foreign policy goals by Nigeria depends on its ability to reactivate the non-oil sector of its economy, particularly the agricultural and manufacturing sectors.